ANALISIS PELAKSANAAN MODEL PEMBELAJARAN NUMBER HEAD TOGETHER (NHT) DAN PENGARUHNYA TERHADAP HASIL BELAJAR IPA - Tri Wiyoko; Munfa'ati Munfa'ati (Jurnal Pendidikan, 2023)
This study aims to analyse the implementation of the Number Head Together (NHT) learning model and its effect on science learning outcomes for fifth grade students at SDN. No. 25/VI Tanjung Ilir, Tabir I District, Merangin Regency. This research is a type of quasi-experimental research (quasi-experimental) with a research design using the One Shot-Case Study. The instruments used are observation sheets of educators and students and 20 multiple choice test questions. The implementation of the Number Head Together (NHT) learning model for educators is 93.75% with a very good category. Furthermore, for the application of the Number Head Together (NHT) learning model to 37.9% students in the very good category and 58.7% in the good category. The average value obtained by students is 78 with 73% completeness. The relationship between the implementation of the Number Head Together (NHT) model with science learning outcomes obtained a value (rs) of 0.545 with a moderate level of relationship. The significance test is based on the value of recount (0.545) > rtable (0.375) then Ho is rejected and Ha is accepted, meaning that there is a relationship between the implementation of the learning process with the NHT model and the science learning outcomes of students in class V. Based on the results of research analysis that the Number Head Together learning model (NHT) has been implemented well so that it has an influence on science learning outcomes in grade V elementary school.